Information System For Thesis Title Submission At The Faculty Of Computer Science, Dehasen University Bengkulu Based On Web Service - Ridwan, Ridwan; Khairil, Khairil; Andry, Ricky Zulfi (Jurnal Media Computer Science, 2024)
The development of science and technology along with the times can support all processes and activities carried out by humans. A computer is a sophisticated tool or electronic object that is broadly composed of hardware and software that work together in processing data that input or by the user. Computers have a lot of features, namely being able to process data in the form of numbers, letters, sounds, symbols, and others. With the existence of computer technology, data processing will be easier and more efficient so that users do not need a long time to manage data. The Information Systems Study Program, Computer Science Faculty, University of Dehasen Bengkulu, is still not effective and efficient in campus services for students who wish to submit their final assignment, especially when submitting thesis titles because they still use the manual method. The study program files are recapitulated one by one into Microsoft Excel, so there is a high risk of data input errors due to human error, not to mention the possibility of duplicate titles that can occur, where the title that has been submitted can be submitted again by another student. This process needs to be supported by the implementation of technology, namely using web as an implementing medium. The writer used PHP programming language and MYSQL database which aims to build an information system for submitting thesis titles which is expected to support and facilitate the process of submitting thesis titles and easily obtain information about campus services, especially when submitting thesis at University of Dehasen Bengkulu.